Extraction and separation of molybdenum(VI) from acidic media by fatty hydrazides - Mohamad, Sharifah; Wan Yunus, Wan Md Zin; Haron, Md Jelas; Ab Rahman, Mohamad Zaki (Wiley Blackwell, 2008)
BACKGROUND: The increasing demand for molybdenum has encouraged the development of low-cost and environmentally friendly extractants to recycle and recover this metal. In the present study, solvent extraction of Mo(VI) from acidic media using a mixture of fatty hydrazides synthesised from palm olein as the extractant was carried out. The effects of various parameters such as acid, diluent, contact time, extractant concentration, metal ion concentration and stripping agent and the separation of Mo(VI) from other metal ions such as Co(II), Ni(II),Al(III) and Mn(II) were investigated.